2011
DOI: 10.1002/j.0022-0337.2011.75.3.tb05042.x
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring of Dental and Dental Hygiene Faculty: A Case Study

Abstract: Given the predicted shortages of dental faculty in the United States, it is important to retain faculty members. Mentoring could play a crucial role in this context. The objectives of this case study were to explore how a six-year mentoring program in the Department of Periodontics and Oral Medicine at the University of Michigan School of Dentistry changed faculty members' perceptions of support from colleagues and their mentoring expectations. In addition, we sought to determine how junior versus senior facul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…[9][10][11] Programs also report using mixed, quantitative, and qualitative methods to assess and better understand the bidirectionality of mentoring relationships as well as secondary effects of mentoring on faculty job satisfaction, perceptions of organizational commitment to scholars, and self-efficacy and confidence in research skills. [12][13][14][15][16][17][18] The importance of a program evaluation is emphasized in a 2012 review of BIRCWH research career development programs, which found that 28 of 29 programs incorporated a structured evaluation of mentoring and training components. 15 The authors emphasized evaluation as a significant strength of the national program.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Programs also report using mixed, quantitative, and qualitative methods to assess and better understand the bidirectionality of mentoring relationships as well as secondary effects of mentoring on faculty job satisfaction, perceptions of organizational commitment to scholars, and self-efficacy and confidence in research skills. [12][13][14][15][16][17][18] The importance of a program evaluation is emphasized in a 2012 review of BIRCWH research career development programs, which found that 28 of 29 programs incorporated a structured evaluation of mentoring and training components. 15 The authors emphasized evaluation as a significant strength of the national program.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the increase in dental hygiene programs comes an increased need for qualified dental hygiene educators. There is a continuing need for health professions educators as documented in the fields of nursing, dentistry, and allied health 2‐4 . Due to this need, educational institutions have come to increasingly rely on part‐time faculty members, also referred to as adjunct or contingent faculty 1,5‐9 .…”
mentioning
confidence: 99%
“…Dental hygiene programs have not been immune to these shortages and have also increased their part‐time faculty members 1 . In spite of the need to recruit and retain dental hygiene educators, 1‐3 there is a distinct lack of research regarding part‐time or adjunct dental hygiene faculty. Do they intend to stay in education, and, if they do not, what factors might influence retention?…”
mentioning
confidence: 99%
“…[5][6][7][8] Mentorship can be defined in many ways in various contexts, all of which encompass a synergistic relationship between a mentor with accumulated expertise and a mentee with novice-like inexperience, who engage in the sharing of knowledge and personal experiences to facilitate career development and guidance towards a path of promotion, fulfilment and overall success. [1][2][3][4][5][6][7][8][9][10][11] Whether formal or informal, mentorship is considered fundamental in an academic career and has both personal and professional effects. [1][2][3][4][5][6][7] In a study by Mylona et al 3 , faculty with mentors were surveyed and reported greater workplace engagement, greater satisfaction with pace of professional advancement, and more positive perceptions of their relationships with colleagues and overall roles within the institution compared to faculty without mentors.…”
mentioning
confidence: 99%